Inversión pública invierte.pe y su relación con el bienestar de la población en el distrito de Iquitos, año 2018 - Apolaya Ríos, Daniel (2021)
The general objective of this research was to determine the relationship between public investment invierte.pe and the welfare of the population of the district of Iquitos, 2018. It is justified by the importance of knowledge and effective management of the destinations of public resources and their impact on the community. The research methodology was quantitative and non-experimental research design - correlational - descriptive. The population was 15 councilors of the Provincial Municipality of Maynas and the sample was 100.0% of the population. The hypothesis posed was: there is a significant relationship between public investment invierte.pe and the welfare of the population of the district of Iquitos, year 2018. A structured questionnaire of 31 questions was used as an instrument, which was applied through the survey technique. As results of the research, it was determined that there is significant correlation between both variables under study, demonstrated by applying the Spearman correlation test where a value of 0.857 and p= 0.025 was obtained with a significance level < 0.05 that allows accepting the hypothesis raised. As conclusions, by virtue of the results, the Provincial Municipality of Maynas through public investment invierte.pe, is not managing to generate 100% of welfare to the population of the district of Iquitos, referred to the closing of gaps (needs), motivated by a disorderly management and attention to properly address public investments.